Productivity of Oil Palm Production Systems in Edo and Kogi States, Nigeria: A Total Factor Productivity Approach - Abdul-Qadir, M. I.; Okoruwa, V. O.; Olajide, A. O. (International Journal of Advanced Science and Technology, 2016)
Self-sufficiency in domestic palm oil supply remains unattainable in Nigeria, despite the various efforts of government to revive the subsector. The contribution of oil palm to employment and income in Nigeria is enormous. However, there is dominance of smallholders, low yield and inadequate documentation on productivity of the Oil Palm Production systems in the country. Thus, this study investigates Total Factor Productivity (TFP) of oil palm production systems in Edo and Kogi States, Nigeria using Tornqvist TFP index. Data were collected by administration of structured questionnaires using multistage sampling procedures. The results showed that the oil palm production in the study area is structured into small (≤ 10 hectare (ha), medium (11 – 50 ha) and large (≥ 51 ha). The TFP of the large, medium and small scale OPPS were 1.04, 0.99 and 0.82, respectively, while the overall TFP was 0.92. The large scale system had the highest productivity, followed by medium scale system in palm oil production in the study areas. Therefore, Promotion incentives should be directed to large and medium scale systems with upgrading of small scale farmers to medium scale farmers.